Examination of DNA sequences undergoing chromatin conformation changes at a variegating breakpoint in Drosophila melanogaster. - Locke, J. (Genetica, 1993)
Position effect variegation in Drosophila melanogaster is associated with the inability of certain genes to be correctly expressed in a proportion of cells, giving a mosaic phenotype. The lack of expression is thought to be due to alterations in the gene's chromatin structure due to its proximity to a region of heterochromatin. Because of the difficulties involved, there is little biochemical data to support the intuitively appealing model of 'heterochromatin spreading' used to explain this phenomenon. Differences in restriction fragment length were used to distinguish DNA regions from either normal (non-position affected) or rearranged (position affected) chromosomes so as to examine possible changes in gene copy number and the effects of endogenous nucleases. DNA sequences at the breakpoint of In(1)wm4, which variegates for the white gene, were assayed under conditions where the chromatin conformation was altered using second site modifier mutations (Su(var) or En(var)). No change in the DNA sequence copy number was observed at either chromosome breakpoint, relative to wild type, when either suppressor or enhancer mutations were present. Therefore copy number change, through differential polyploidization or somatic gene loss, is not affected by Su(var) or En(var) induced changes in the chromatin conformation. Initial experiments showed a gross difference in the sensitivity of DNA to endogenous nucleases that appeared associated with Su(var) and En(var) mutations. En(var) mutation bearing samples appeared delayed in the digestion, relative to Su(var).(ABSTRACT TRUNCATED AT 250 WORDS)